Teun A. Van Dijk's critical discourse analysis of the Palestinian resistance poetry Lam Yabqo Hibrun by Maisa Abd Elhadi - R.U., Nafisatul Izza; Kholisin, Kholisin; Aminy, Annisa Octaria (Fakultas Sastra Universitas Negeri Malang, 2024)
The prolonged conflict between Palestine and Israel has caused suffering and deep wounds in Palestinian society. However, amid this suffering, the Palestinians showed extraordinary resilience and a strong spirit of resistance. This study aims to analyze the text structure, social cognition, and social context in the Palestinian resistance poem Lam Yabqo Hibrun. The research data sources come from literature studies and internet searches. This research includes descriptive qualitative research with data collection techniques through documentation with Van Dijk's critical paradigm model. The data analysis technique includes data redaction, presentation, and conclusion drawing. The results of the research using the Teun A. van Djik model are (1) macro-structure; (2) superstructure, and (3) microstructure. Based on the critical discourse analysis of the poem Lam Yabqo Hibrun, it can be concluded that the information con-veyed meets the critical analysis level of Teun A. van Dijk's model (1) text structure; (2) social cognition and (3) social context. This research implies the spirit of Palestinian resistance to the oppression they face, as well as expressing a longing for freedom and justice, using metaphorical images of Jerusalem as the centre of the struggle and destruction experienced by the Palestinian people.